Can the periphery speak? A critical rereading of the cultural production of the peripheries - Silvio Rogério dos Santos (Geografares, 2022)
In this article, I seek to make a critical rereading of the cultural production of the peripheries and its relationship with the “system”, that is, with the established power. From the financing used by such production, whether public or private, as well as their partnerships and the consequences resulting from these links, I seek to reflect on the political, cultural and subjective impacts in the context of the peripheries. Taking as a starting point the seminal works on the subject, as well as the “pedagogical, aesthetic and political project” (NASCIMENTO, 2009) derived from this production, I raise some questions that I think are interesting, to think about culture, politics and peripheries in the current context, reflecting on the incidence of neoliberal/neocolonial logic in culture, based on the research I have been developing since 2016 with Coletivos Periftividade and Poesia na Brasa and more recently with Casa Ecoativa and collective Imargem, in São Paulo.
Keywords: culture; power; peripheries